Antimicrobial functional divergence of the cecropin antibacterial peptide gene family in Musca domestica - Peng, Jian (Parasit Vectors, 2019)
BACKGROUND: It has been reported that there are more than ten antimicrobial peptides (AMPs) belonging to the cecropin family in Musca domestica; however, few of them have been identified, and the functions of the other molecules are poorly understood. METHODS: Sequences of the M. domestica cecropin family of genes were cloned from cDNA template, which was reverse-transcribed from total mRNA isolated from third-instar larvae of M. domestica that were challenged with pathogens. Sequence analysis was performed using DNAMAN comprehensive analysis software, and a molecular phylogenetic tree of the cecropin family was constructed using the Neighbour-Joining method in MEGA v.5.0 according to the mature peptide sequences. Antibacterial activity of the synthetic M. domestica cecropin protein was detected and the minimum inhibitory concentration (MIC) values were determined using broth microdilution techniques. Time-killing assays were performed on the Gram-negative bacteria, Acinetobacter baumannii, at the logarithmic or stabilizing stages of growth, and its morphological changes when treated with Cec4 were assessed by scanning electron microscopy (SEM) and detection of leakage of 260 nm absorbing material. RESULTS: Eleven cecropin family genes, namely Cec01, Cec02 and Cec1-9, show homology to the Cec form in a multigene family on the Scaffold18749 of M. domestica. In comparing the encoded cecropin protein sequences, most of them have the basic characteristics of the cecropin family, containing 19 conservative amino acid residues. To our knowledge, this is the first experimental demonstration that most genes in the Cec family are functional. Cec02, Cec1, Cec2, Cec5 and Cec7 have similar antibacterial spectra and antibacterial effects against Gram-negative bacteria, while Cec4 displays a more broad-spectrum of antimicrobial activity and has a very strong effect on A. baumannii. Cec4 eliminated A. baumannii in a rapid and concentration-dependent manner, with antibacterial effects within 24 h at 1× MIC and 2× MIC. Furthermore, SEM analysis and the leakage of 260 nm absorbing material detection indicated that Cec4 sterilized the bacteria through the disruption of cell membrane integrity. CONCLUSIONS: Although there are more than ten cecropin genes related to M. domestica, some of them have no preferred antibacterial activity other than Cec4 against A. baumannii.